Norms of Violence in Byzantine Civil Wars (976 – 1081) - NEUHAUSER, Arie (Byzantina Symmeikta, 2025)
This paper seeks to identify the norms governing violence, especially against non-combatants, in the civil wars of Byzantium during the eleventh century, from the accession of Basil II in 976 to that of Alexios I Komnenos in 1081. While civil wars and their justifications have attracted much attention from scholars in the field, this is the first study dedicated to the topic of conduct during internal military conflicts. Making use of the concept of Spielregeln (“rules of the game”) that was articulated by the historian of the western Middle Ages Gerd Althoff, it argues that cultural standards against violence inflicted on fellow Romans had a tangible effect on the conduct of the opposing sides in civil wars.